Interrupted aortic arch with isolated persistent left superior vena cava in patient with Turners syndrome - M Obadah Kattea (Thieme Medical and Scientific Publishers Pvt. Ltd., 2016)
We present a case of 13-year-old female with Turner syndrome (TS), who presented with unexplained lower limbs swelling and ejection systolic murmur at the left second intercostal space. Suspicion of mild aortic coarctation was made by echocardiography. Computed tomography angiography (CTA) showed a complete interruption of the aortic arch (IAA) below the left subclavian artery with persistent left superior vena cava (PLSVC) and absent right SVC, defined as an isolated PLSVC. The patient underwent successful surgical correction after unsuccessful trial of transcatheter stent placement. We present this case of asymptomatic IAA to draw attention to the importance of CTA in diagnosing such rare anomalies and ruling out asymptomatic major cardiovascular abnormalities in patient with TS.